Ethical Leadership And Voice Behavior: Mediating Psychological Safety And Ethical Culture - Haznil Zainal; Agustin Basriani; Adi Rahmat; Elmi Yadi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study aimed to determine the role of organizational ethical culture and psychological safety in moderating the relationship between ethical leadership and lecturers' voice conduct. The study hypothesis is investigated with WarpPLS software employing descriptive analysis, confirmatory and structural equation modelling (SEM). This survey included 196 economic instructors from ten private universities in Pekanbaru. Organizational ethical culture, psychological safety, and faculty voice conduct were positively connected to Ethical Leadership (EL). Using one's voice is related to Ethical Culture (EC) and Psychological Safety (PS). EC and PS mediate the relationship between EL and Voice Behaviour (VB). EC and PS mitigate the effect on the link between ethics and PS.